Intercultural Competence in Teaching: Defining the Intercultural Profile of Student Teachers - Marta Garrote Salazar (Universitat Autònoma de Barcelona, 2016)
This article describes the intercultural profile of European student teachers in order to clarify the relationship between Intercultural Competence (IC) and teacher training. The main tool used for that was a questionnaire to assess IC, following the criteria established by the Intercultural Competence Assessment (INCA) Project in which IC levels are ranked. The survey poses a variety of personal and professional situations where IC comes into play and different responses to choose from, ranging from insufficiently intercultural to highly intercultural. The results of this study show that most European student teachers participating in the research displayed an intermediate level of IC, which indicates a necessity to improve future teachers’ IC training, particularly highlighting IC dimensions such as behavioural flexibility or communicative awareness.